2022
DOI: 10.1001/jamaophthalmol.2022.2757
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Open Payments–Reported Industry Transfers of Value and Prostaglandin Analog Prescribing in the US

Abstract: Key Points Question Are transfers of value (TOV) reported by makers of branded prostaglandin analog (PGA) eye drops associated with a greater likelihood of prescribing branded PGAs? Findings In this cohort study, recipients of TOV were more likely to prescribe branded PGAs compared to prescribers with no reported TOV, even with a relatively low TOV median. A dose-response association was observed, which was robust even when excluding prescribers with the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Further, the authors point out that other research has not shown an increase in clinical effectiveness or reduction in adverse effects with the newer branded PGAs compared with the generic. 1 The authors also note that data suggests that patients who are prescribed the lower-cost generic…”
Section: Invited Commentarymentioning
confidence: 99%
See 4 more Smart Citations
“…Further, the authors point out that other research has not shown an increase in clinical effectiveness or reduction in adverse effects with the newer branded PGAs compared with the generic. 1 The authors also note that data suggests that patients who are prescribed the lower-cost generic…”
Section: Invited Commentarymentioning
confidence: 99%
“…Small Payments, Large Consequences Roni M. Shtein, MD, MS; Paul R. Lichter, MD, MS; Paul P. Lee, MD, JD In this issue of JAMA Ophthalmology, Nguyen et al 1 report on the potential association of industry payments to optometrists and ophthalmologists with the prescription of branded to generic prostaglandin analogs (PGA) for treating glaucoma. In their retrospective Medicare database analysis, the authors elegantly combined drug prescribing information from the US Centers for Medicare & Medicaid Services (CMS) Part D beneficiary database with CMS Open Payments data about industry payments using a ProPublica crosswalk to align prescriber information between the 2 databases.…”
Section: Invited Commentarymentioning
confidence: 99%
See 3 more Smart Citations